2014
DOI: 10.1155/2014/592379
|View full text |Cite
|
Sign up to set email alerts
|

Postinduction Supportive Care of Pediatric Acute Myelocytic Leukemia: Should Patients be Kept in the Hospital?

Abstract: Children with AML become profoundly neutropenic while they undergo remission induction chemotherapy. It is unknown whether these children should be kept in the hospital while they are severely neutropenic to prevent life-threatening complications associated with neutropenia and reduce fatality. We at our institution routinely discharge patients after completing remission induction chemotherapy in the presence of profound neutropenia, unless it is clinically contraindicated. We reviewed all AML patients who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…This variation in practice is consistent with a recent survey of supportive care approaches among COG institutions and likely reflects the dearth of studies to compare the effectiveness of the two strategies in pediatric AML populations. One pediatric study found similar rates of mortality for outpatient versus inpatient management of neutropenia following AML induction chemotherapy which is consistent with our findings. Another study evaluating outpatient versus inpatient AML intensification chemotherapy found fewer days of febrile neutropenia and less antimicrobial use among outpatients than children receiving inpatient treatment .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This variation in practice is consistent with a recent survey of supportive care approaches among COG institutions and likely reflects the dearth of studies to compare the effectiveness of the two strategies in pediatric AML populations. One pediatric study found similar rates of mortality for outpatient versus inpatient management of neutropenia following AML induction chemotherapy which is consistent with our findings. Another study evaluating outpatient versus inpatient AML intensification chemotherapy found fewer days of febrile neutropenia and less antimicrobial use among outpatients than children receiving inpatient treatment .…”
Section: Discussionsupporting
confidence: 90%
“…However, a recent survey of pediatric supportive care practices suggests that up to one‐third of pediatric AML patients are discharged early to outpatient management during postchemotherapy neutropenia . While outpatient supportive care in this population has only been examined in a single study of 26 patients , several studies of adult AML patient populations suggest that outpatient management during neutropenia may be safe and feasible . Early hospital discharge was associated with fewer febrile episodes , reduced use of intravenous antibiotics and comparable mortality .…”
Section: Introductionmentioning
confidence: 99%
“…Pediatric patients with AML traditionally remain hospitalized during treatment courses until ANC recovery to reduce infectious complications. However, studies suggest that outpatient management is safe and feasible for low‐risk adult and pediatric patients with AML . Furthermore, studies assessing the outpatient management of febrile neutropenia in adult and pediatric cancer populations and home chemotherapy treatment for pediatric ALL demonstrate reduced costs and improved quality of life for patients and their families .…”
Section: Discussionmentioning
confidence: 99%
“…However, studies suggest that outpatient management is safe and feasible for low-risk adult and pediatric patients with AML. [23][24][25][26] Furthermore, studies assessing the outpatient management of febrile neutropenia in adult and pediatric cancer populations and home chemotherapy treatment for pediatric ALL demonstrate reduced costs and improved quality of life for patients and their families. [27][28][29][30][31] In this context, our results suggest that judicious use of outpatient management may have distinct advantages, including cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…The difference was not significant (P = 0.59). However, it has been demonstrated that [28][29][30] , no matter AL patient achieves CR after chemotherapy, or the patient was without clinical contraindications, and even with severe neutropenia, it could not affect the discharge. But we need more clinical validation to confirm this conclusion.…”
Section: Discussionmentioning
confidence: 99%